Changing goals in the management of breast carcinoma patients towards preservation of feminity and quality of life - Pathak, Soumi; Bhargava, Ajay Kumar (Journal of Society of Anesthesiologists of Nepal, 2018)
Breast cancer is the commonest cancer in women worldwide. In the developing countries of Asia, the health care burden on account of breast cancer has been steadily mounting. Over 100,000 new breast cancer patients are estimated to be diagnosed annually in India.1 As per the ICMR-PBCR data, breast cancer is the commonest cancer among women in urban registries of Delhi, Mumbai, Ahmedabad, Calcutta, and Trivandrum where it constitutes > 30% of all cancers in females. Previous literature on mastectomy indicates that the operation may be perceived by the patient as a threat to her feminity. Breast cancer survivors have dissatisfaction with appearance, perceived loss of femininity and body integrity, self-consciousness about appearance, and dissatisfaction with surgical scars… Journal of Society of Anesthesiologists of Nepal Vol. 4, No. 2, 2017, Page: 96-98